Multi-decadal sea level trends and land movements in the Mediterranean Sea with estimates of factors perturbing tide gauge data and cumulative uncertainties - Tsimplis, M.; Spada, G.; Marcos, M.; Flemming, N. (Global and planetary change, 2011)
Sea level trends in the Mediterranean Sea and their forcing parameters are explored. Multi-decadal trends from available tide gauge records are estimated together with the contribution of the oceanic (steric and mass variations) and atmospheric (pressure and wind) changes as well as land movements (including GIA). Each forcing factor is considered as an independent process creating its own signal on a tide gauge, and subject to uncertainties of measurement, deduction or interpretation of proxy data for that factor. The paper is focused on the uncertainty of the estimate of each forcing factor, including the estimate of the eustatic part affecting the Mediterranean Sea, obtained by subtracting GIA and land movements obtained from geomorphological and archaeological data at the tide gauge stations.